2003
DOI: 10.1094/phyto.2003.93.5.564
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Postharvest Biocontrol Yeasts to Oxidative Stress: A Possible New Mechanism of Action

Abstract: We detected the generation of the reactive oxygen species (ROS) superoxide anion ( O.(-) (2)) and hydrogen peroxide (H(2)O(2)) in apple wounds 2 immediately after wounding, and assessed the relationships between (i) timely colonization of apple wounds by biocontrol yeasts, (ii) resistance of these microorganisms to oxidative stress caused by ROS, and (iii) their antagonism against postharvest wound pathogens. We analyzed a model system consisting of two yeasts with higher (Cryptococcus laurentii LS-28) or lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 22 publications
3
90
0
2
Order By: Relevance
“…The isolates were incubated on potato dextrose agar (PDA; Difco) for 7 days at 30°C, before use. Twenty-five milliliters of potato dextrose broth (PDB; Difco) (which is aflatoxin conducive) in 50-ml Erlenmeyer flasks was inoculated with the WT, ⌴, and CM strains, using 0.2 ml of conidial suspension (ϳ10 6 conidia) for each flask; incubation was performed at 30°C for different time periods (10,12,14,18,21,24,30,36,42,48,60,72,96,120,144, and 168 h). In other experiments, 50 ml of Czapek Dox (CD) broth (Difco) (which is low-conducive for aflatoxins) was inoculated with the WT and M strains; after 4 days of incubation at 30°C, 1 mM cumene hydroperoxide (CH), 0.5 mM menadione (Men), and 1 mM and 10 mM hydrogen peroxide (H 2 O 2 ) were added to test the strain's sensitivity to oxidant stressors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates were incubated on potato dextrose agar (PDA; Difco) for 7 days at 30°C, before use. Twenty-five milliliters of potato dextrose broth (PDB; Difco) (which is aflatoxin conducive) in 50-ml Erlenmeyer flasks was inoculated with the WT, ⌴, and CM strains, using 0.2 ml of conidial suspension (ϳ10 6 conidia) for each flask; incubation was performed at 30°C for different time periods (10,12,14,18,21,24,30,36,42,48,60,72,96,120,144, and 168 h). In other experiments, 50 ml of Czapek Dox (CD) broth (Difco) (which is low-conducive for aflatoxins) was inoculated with the WT and M strains; after 4 days of incubation at 30°C, 1 mM cumene hydroperoxide (CH), 0.5 mM menadione (Men), and 1 mM and 10 mM hydrogen peroxide (H 2 O 2 ) were added to test the strain's sensitivity to oxidant stressors.…”
Section: Methodsmentioning
confidence: 99%
“…In Aspergillus nidulans, the presence of the fatty-acid DOXs PpoA, -B, and -C has been reported (63). In Aspergillus, compounds produced by LOXs and DOXs, such as hydroperoxyoctadecadienoic acid (HPODE) and precocious sexual inducer factors, which consist of a mixture of hydroxylated oleic, linoleic, and linolenic acids, have all been shown to stimulate conidiogenesis, and in Aspergillus flavus this occurrence is related to aflatoxin biosynthesis (7,10,12,13). In A. nidulans, ROS can also steer the production of mitospores and meiospores in the regulation of the asexual and sexual phases in development (25,63).…”
mentioning
confidence: 99%
“…It has been reported that peroxidases and superoxide dismutase in grapefruit were induced by application of the yeast M. fructicola, based on transcriptome analysis (56). Castoria et al (39) investigated the relationship between oxidative stress resistance and the fitness of the postharvest biocontrol yeasts Cryptococcus laurentii LS-28 and Rhodotorula glutinis LS-11 (39). C. laurentii LS-28, which had higher resistance to ROS-generated oxidative stress than R. glutinis LS-11, exhibited greater colonization and better biocontrol efficacy on apple fruit.…”
Section: Environmental Stressesmentioning
confidence: 99%
“…In some cases, biotransformation leads to less toxic or non-toxic products and is considered to be a detoxification (He et al 2010;Karlovsky 1999;Wu et al 2009). The yeast R. kratochvilovae (formerly Rhodotorula glutinis) strain LS11 is an excellent biocontrol agent of P. expansum (Castoria et al 2003(Castoria et al , 2005Lima et al 2003, …”
Section: Introductionmentioning
confidence: 99%